2011
DOI: 10.1097/fjc.0b013e31821823d9
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Myocardial Fibrosis

Abstract: Increased cardiac collagen deposition is observed in almost every cardiac disease and plays an important role in the deteriorating function of the diseased heart. Propeptides of procollagen types I and III, the 2 major collagen types in the heart, can be detected in circulation. Although these propeptides reflect collagen synthesis, also breakdown products of collagen and the matrix metalloproteinases, responsible for the breakdown of the extracellular matrix, can be detected in blood and are used for investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
81
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 80 publications
2
81
0
3
Order By: Relevance
“…In heart diseases, chronic neurohormonal stimulation can result in the deposition of interstitial connective tissue (i.e., reactive fibrosis) as well as myocardial necrosis followed by fibrous tissue formation (i.e., reparative fibrosis) 33, 34. A study in humans with dilated cardiomyopathy indicated that deposition of interstitial collagen may cause deterioration in ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…In heart diseases, chronic neurohormonal stimulation can result in the deposition of interstitial connective tissue (i.e., reactive fibrosis) as well as myocardial necrosis followed by fibrous tissue formation (i.e., reparative fibrosis) 33, 34. A study in humans with dilated cardiomyopathy indicated that deposition of interstitial collagen may cause deterioration in ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that the activation of hypertrophic markers, matrix metalloproteinases (MMPs), and proinflammatory cytokines play a central pathophysiological roles in the development of cardiac hypertrophy, fibrosis, and heart failure in the experimental animal models and humans (11,52,58,66). Previous studies have suggested that ANP/ NPRA signaling acts as a negative regulator of inflammation and hypertrophic growth (14,65,67,69).…”
mentioning
confidence: 99%
“…1 The extent of fibrosis and collagen scar is an important factor in the assessment of interventions aimed at treating cardiac diseases. 2 Hence an efficient and reliable measurement of collagen deposition in cardiac tissue is of great interest in the assessment of treatment strategies for cardiac pathologies. Because of several limitations and the variability experienced in staining techniques, we propose an alternative FT-IRIS methodology for detection and characterization of collagen deposition in cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac tissue, this matrix supports, connects, and coordinates cardiac myocytes and the forces generated by them. 1,2 Several cardiac pathologies are associated with significant changes in the composition of the matrix. 1,2 Therefore, detection and quantitative measurement of these matrix changes play an important role in experimental assessment of novel treatment methods and drug delivery systems for treating cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation